Responses to irregularly staying migrants in Ireland - Michał Polakowski; Emma Quinn (The Economic and Social Research Institute (ESRI), 2022)
Irregularly staying migrants are more likely to face material deprivation, instability and are more vulnerable to exploitation and crime than legal residents (FRA, 2011). Ultimately, they may face deportation to their country of origin. The fear of detection and deportation can lead to underutilisation of public services (Vintila and Lafleur, 2020). The recent introduction of the Regularisation of Long-Term Undocumented Migrants Scheme (discussed below) is a major policy development that should improve the situation of many people living in Ireland. However, it is likely that irregular migration will persist, and related policy challenges will remain. This report aims to provide an overview of the situation of irregularly staying migrants in Ireland, including access to public services, and to outline major public debates and policy measures introduced to address related issues.
Keywords: 330; Illegale Migration; Soziale Lage; Öffentliche Dienstleistung; Migrationspolitik; Einwanderungsrecht; Irland